The Myths of Health Care Towards New Models of Leadership and Management in the Healthcare Sector (Springer International Publishing, 2018)
This provocative appraisal unpacks commonly held beliefs about healthcare management and replaces them with practical strategies and realistic policy goals. Using Henry Mintzberg's "Myths of Healthcare" as a springboard, it reveals management practices that undermine care delivery, explores their cultural and corporate origins, and details how they may be reversed through changes in management strategy, organization, scale, and style. Tackling conventional wisdom about decision-making, cost-effectiveness, service quality, and equity, contributors fine-tune concepts of mission and vision by promoting collaboration, engagement, and common sense. The book's multidisciplinary panel of experts analyzes the most popular healthcare management "myths," among them: · The healthcare system is failing. · The healthcare system can be fixed through social engineering. · Healthcare institutions can be fixed by bringing in the heroic leader. · The healthcare system can be fixed by treating it more as a business. · Healthcare is rightly left to the private sector, for the sake of efficiency. The Myths of Health Care speaks to a large, diverse audience: scholars of all levels interested in the research in health policy and management, graduate and under-graduate students attending courses in leadership and management of public sector organization, and practitioners in the field of health care.